Prospek Pengembangan Agroindustri Minyak Nilam - Muhammad Qori Husein; Gustami Harahap; Mitra Musika Lubis (Jurnal Ilmiah Pertanian ( JIPERTA), 2019)
The purpose of this study was to determine the feasibility of development of patchouli oil And to identify factors - factors that affect demand for patchouli oil. The sampling method used is a census that is all patchouli oil farmers owning patchouli oil fields and refining. Data Analysis Method used is Cost Analysis.The results showed that the location of patchouli oil refining research effort by the farmers financially feasible to be developed because Value B / C ratio for patchouli oil refining business is 2.28 where the B / C 1, the average profit earned patchouli oil farmers is Rp 45,115,675 / growing season, NPV for patchouli oil refining business is Rp 41,390,526 with interest rate loan or business credit (KUR) is 9% and an initial investment of Rp 19,774,458. Factors that influence patchouli oil are patchouli oil prices and income of patchouli oil farmers but the factors that have a significant effect on patchouli oil production are income, while oil prices have no significant effect on patchouli oil production.